The performance of Asian Hedge Funds - Shi, Wenjie (2017)
This paper focus on the correlation between major macro indicators and the Asian hedge funds performance. The author introduces a Vector Auto regression model to find this correlation and proposes a method to forecast the hedge fund return. It is found that the government Treasury bill interest rate has the largest influence on the return, even bigger than the money market rate. Exchange rate has an insignificant correlation with the return, while the sign of the coefficient meets the expectation. When money market rate, Treasury bill rate and exchange rate increases, the return for the hedge funds decreases. However, the actuation duration is different among the three indicators. Money market rate takes two months. Treasury bill rate takes one month, and exchange rate takes five months. Moreover, both three macro indicators are good for forecasting the hedge funds performance under the Vector Auto regression model. Finally, policy implication and discussion are given.